Effect of Postnatal Magnesium Sulfate Infusion on Neurological Outcome of Term Neonates with Severe Perinatal Asphyxia - Tariq Mahmood,Rubina Zulfiqar,Tanzeela Farah,Tariq Saeed (Journal of Rawalpindi Medical College, 2015)
Background : To compare magnesium sulfate with placebo in term neonates with moderate to severe ischemic encephalopathy due to severe perinatal asphyxia in term of improved neurological outcome. Methods: In this randomized controlled trial a total of seventy term neonates of age less than six hours of either sex suffering from moderate and severe hypoxic ischemic encephalopathy were included. Neonates were assessed at two different ages , 2-3 hours and 4-5 hours, respectively. Each patient remained in the hospital for at least 14 days. Patients were randomly divided into two groups A and B. Group A received magnesium sulphate at 250 mg/kg/dose ( 1 ml/kg/ dose in 20 ml of 5% dextrose water) over one hour with the additional doses repeated at interval of 24 hours and 48 hours. Group B received 1 ml/kg/dose of normal saline in 20 ml of 5% dextrose water. (Three doses , 24 hours apart). Serum magnesium levels were carried out at seventy two hours of life. .Monitoring was also done for clinical course of encephalopathy, laboratory variables and adverse effects. At the time of discharge ,neurological examination was carried out and CT scan was done at fourteenth day of life. Results:- More infants in group A were sucking at discharge as compared to group B (71.4℅ vs 40℅; p=0.008). Neuroimaging (CT scan on day 14th) yielded abnormal findings for fewer neonates in group A which was significantly low as compared to group B (11.4% vs 37.1℅ p= 0.012). Conclusion: Postnatal magnesium sulfate infusion is effective in improving outcome for infants with severe perinatal asphyxia.